Śląscy prawnicy o autonomii śląskiej w Drugiej Rzeczypospolitej - Krychowski, Adam (L'vìvs'kij nacìnal'nij unìversitet ìmenì Ìvana Franka, 2019)
Upper Silesia occupied a special place in the history of the Second Polish Republic. It resulted from a very long and complicated road to rejoin Poland. This region was of great importance to Poland because of its industry. In the background of the rest of the country, it was also distinguished by its autonomy. Legal and political solutions applied in Upper Silesia were developed to a large extent thanks to local lawyers. Among those best known were Włodzimierz Dąbrowski, who sought the legal unification of the Śląskie Voivodeship with the rest of Poland. It must be emphasized that he did not criticize autonomy as such. He stressed its good sides and drew attention to those aspects that should be preserved. It is also worth paying attention to Paweł Kempka, who is largely responsible for administrative and tax solutions in Upper Silesia. In this article, there must be also space for Konstanty Wolny, who was the Marshal of the Silesian Parliament. He was also one of the main creators of the organic statute and a keen advocate of Silesian autonomy. It should be noted that, of course, a group of Silesian lawyers worthy of commemoration and deserving closer acquaintance with their biographies is, of course, definitely wider.
Keywords: Górny Ślask; autonomia Śląska; II Rzeczpospolita; województwo śląskie; prawnicy; samorząd